Secretase promotes AD progression: simultaneously cleave Notch and APP - Yang, Ke-Fan; Zhang, Jing-Yi; Feng, Mei; Yao, Kuo; Liu, Yue-Yang; Zhou, Ming-Sheng; Jia, Hui (Frontiers in Aging Neuroscience, 2024)
Alzheimer’s disease (AD) involves complex pathological mechanisms. Secretases include membrane protein extracellular structural domain proteases and intramembrane proteases that cleave the topology to type I or type II. Secretases can effectively regulate the activation of Notch and amyloid precursor protein (APP), key factors in the progression of AD and cancer. This article systematically summarizes the intracellular localization, cleavage sites and products, and biological functions of six subtypes of secretases (α-secretase, β-secretase, γ-secretase, δ-secretase, ε-secretase, and η-secretase), and for the first time, elucidates the commonalities and differences between these subtypes of secretases. We found that each subtype of secretase primarily cleaves APP and Notch as substrates, regulating Aβ levels through APP cleavage to impact the progression of AD, while also cleaving Notch receptors to affect cancer progression. Finally, we review the chemical structures, indications, and research stages of various secretase inhibitors, emphasizing the promising development of secretase inhibitors in the fields of cancer and AD.